2016
DOI: 10.1016/j.bbagrm.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Core promoter-specific gene regulation: TATA box selectivity and Initiator-dependent bi-directionality of serum response factor-activated transcription

Abstract: Gene-specific activation by enhancers involves their communication with the basal RNA polymerase II transcription machinery at the core promoter. Core promoters are diverse and may contain a variety of sequence elements such as the TATA box, the Initiator (INR), and the downstream promoter element (DPE) recognized, respectively, by the TATA-binding protein (TBP) and TBP-associated factors of the TFIID complex. Core promoter elements contribute to the gene selectivity of enhancers, and INR/DPE-specific enhancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 71 publications
0
17
0
1
Order By: Relevance
“…3B). The physiological basis for the differential expression of tdTomato from this transgene is unknown, but might relate to SRF/MRTF-binding sites in the chick ACTB promoter within the CAG construct and the differential activity of these actin levelsensitive transcription factors (Knöll, 2010;Xu et al, 2016) in various cell types of the developing kidney. RNA sequencing (RNA-seq) was used to define these populations obtained from control and Eed mutant mice by FACS (Table S1, Fig.…”
Section: Nephron Differentiation In Eed Mutant Micementioning
confidence: 99%
“…3B). The physiological basis for the differential expression of tdTomato from this transgene is unknown, but might relate to SRF/MRTF-binding sites in the chick ACTB promoter within the CAG construct and the differential activity of these actin levelsensitive transcription factors (Knöll, 2010;Xu et al, 2016) in various cell types of the developing kidney. RNA sequencing (RNA-seq) was used to define these populations obtained from control and Eed mutant mice by FACS (Table S1, Fig.…”
Section: Nephron Differentiation In Eed Mutant Micementioning
confidence: 99%
“…In human case, 24% of genes have promoter regions containing TATA-box (Yang et al, 2007). In eukaryotes, TATA-box is located at ~25 bp upstream of the TSS (Xu et al, 2016). It is able to define the direction of transcription and also indicates the DNA strand to be read.…”
Section: Introductionmentioning
confidence: 99%
“…MEF2 site is essential for the amplification of Mef2c involved in skeletal muscle development [22]. Additionally, analysis of the promoters of the actin-related group of serum response factor (SRF) with scaffolding or contractile functions has indicated that approximately 43% of the involved genes in the mouse contains TATA box sequences within the core promoter region [23]. In a cascade regulation process induced by the cytokine transforming growth factor beta (TGF-β), E2A immunoglobulin enhancer-binding factors E12 and E47 regulate palladin cytoskeletal protein [24].…”
Section: Discussionmentioning
confidence: 99%